Growth, Degrowth or Post-growth? Towards a synthetic understanding of the growth debate - Xhulia Likaj; Michael Jacobs; Thomas Fricke (Forum for a New Economy, 2022)
Arguments about the possibility and desirability of exponential economic growth have animated the environmental movement for half a century, since the publication of the Club of Rome report The Limits to Growth in 1972. The debate has been revived in recent years as the climate crisis has reached centre-stage. This paper seeks to unpick the different strands in the debate and the different kinds of arguments - philosophical, empirical, and policy-prescriptive - used by different writers and institutions. It suggests that the contemporary debate is best understood as a disagreement between political strategies, in which the character of public and academic discourse plays a key role.
Keywords: O4; O44; Q45; Q56; 330; economic growth; green growth; degrowth; post-growth; wellbeing; GDP